Feasibility study of dual-function chemical in reducing surfactant adsorption and interfacial tension for chemical enhanced oil recovery application - Akhir, N.A.M. (Offshore Technology Conference, 2020)
The performance of a low-cost and biodegradable dual-function chemical was evaluated based on its attainment in reducing the interfacial tension and surfactant adsorption in the synthetic seawater at the temperature of more than 90°C. The phase behaviour, interfacial tension, and static adsorption tests have been conducted for the feasibility study of dual-function chemical for the chemical enhanced oil recovery application. The experimental matrices were constructed using Design Expert. Anionic and amphoteric surfactants have been identified for the study to be tested with the dual-function chemical at the temperature more than 90°C in the synthetic seawater. In the phase behaviour study, the volume ratio of the aqueous phase to the Malaysian crude oil was kept 1:1. The interfacial tension between the surfactant and dual-function chemical system against the crude oil was performed by using a spinning drop method. Meanwhile, the static adsorption was conducted by using the crushed core at room temperature up to 30 days, the analysis was conducted by using High-Performance Liquid Chromatography (HPLC) method. In comparison with two types of surfactants; the dual function chemical works best with the anionic surfactant in order to reach the ultralow interfacial tension (less than 10-3 mN/m) within 60 minutes. The ultralow interfacial tension for amphoteric surfactant can only be obtained at an earlier time. In contrast, the phase behaviour study for anionic and amphoteric surfactants and dual-function chemical obtained was a Type II(-) microemulsion. In the static adsorption study, the dual-function chemical (>0.5 wt.) significantly helps in reducing the adsorption of anionic and amphoteric surfactants up to 73. Based on the obtained results, dual-function chemical works efficiently when compounded with anionic surfactant than amphoteric surfactant at the same surfactant concentration and reservoir conditions. Copyright © 2020, Offshore Technology Conference.